Profile Evaluation in Indonesia: The Encouragement of Educational Change Facing the Era of Digitalism - Paisal, Manurung; Yen, Aryni (LPPM Undiksha, 2019)
Education contribution to the formation of the style and quality of the future of human civilization can not be denied again. Education conventionally until the modern age was still believed to be a strategic location to expand the horizons and to provide the most valuable information about the meaning and purposing of life as the norm was taken. It needed that were essential to face the challenges of the changes in the future to create individuals, communities, and nations. While education digitalism was a very effective system to improve the quality of human life in all aspects of human life, education presented conscious efforts. Encouragement of education not only in preparing personnel professional teachers in their field but also encouraged prepared proteges facing to change towards conventional for digitalism. A fundamental change in the framework of preparing students was: change's ideology, self-control, futuristic effect, meaning in life.